A Detailed Investigation Into the Wave Energy Resource at a Small-Scale Ocean Energy Test Site in China - Fang, Yizhou; Wu, He; Zhou, Qingwei; Jiang, Bo; Wang, Xiaoyong (Frontiers in Energy Research, 2022)
During the R&D of marine renewable energy converters, scale models are usually used in the early stages of development of marine renewable energy converters. China’s National Ocean Integrated Test Site (NOITS) is being developed by the National Ocean Technology Center (NOTC) in Weihai, Shandong Province, to facilitate testing of scaled wave and tidal energy converters in an open sea environment. This research aims to gain a detailed understanding of the wave characteristics and the wave energy resource at this site. A nested modeling system has been implemented using Simulating WAves Nearshore (SWAN) to provide a 10-year high-resolution wave hindcast between 2009 and 2019 with an approximately 60 m resolution covering the test site. Analysis of the spatio-temporal distribution of wave energy resource in NOITS reveals its strong seasonality, with the mean wave power density of >1.5 kW/m during winter and <0.2 kW/m during summer. We also performed a statistical analysis of the high and extreme wave conditions and their occurrence. By applying scaling methods to wave resources, four WECs were selected to demonstrate the testing at different scale ratios in NOITS. The results of this study provide engineering references for the design of scale wave energy converter models which target to perform open sea trials in NOITS.